Prenatal Mouth Movements: Can We Identify Co-Ordinated Fetal Mouth and LIP Actions Necessary for Feeding? - Nadja Reissland; Claire Mason; Benoist Schaal; Karen Lincoln (International Journal of Pediatrics)
Observations of prenatal movement patterns of mouth and lips essential for feeding could have the potential for an assessment of the readiness to feed after birth. Although there is some research on sucking per se, we know very little about prenatal preparatory movements for sucking, namely, the ability to co-ordinate opening the mouth widely and then pursing the lips as if around a teat or nipple in utero. The purpose of the present study was to test two hypotheses using an adapted version of the Facial Action Coding Scheme: first that mouth stretch (AU 27) will be followed by lip pucker (AU 18), and second that these coordinated movement patterns will increase as a function of gestational age. Fifteen healthy fetuses were scanned four times between 24 and 36 weeks gestation using 4D ultrasound visualization. Results showed a decreased number of mouth stretches with increasing fetal age. Contrary to our expectations, we did not find an increase in movement patterns of mouth stretch followed by lip pucker in preparation for feeding ex utero. The results are discussed in terms of sensory triggers in utero required to elicit preparatory movements for feeding ex utero.